Enhanced critical current density of ex situ MgB2 via control of Mg assisted sintering - Mohd Hapipi, Nurhidayah; Chen, Soo Kien; Shaari, Abdul Halim; Awang Kechik, Mohd Mustafa; Lim, Kean Pah; Tan, Kar Ban; Lee, Oon Jew; Arvapalli, Sai Srikanth; Miryala, Muralidhar (Springer, 2022)
In this work, ex situ MgB2 was mixed with 0.5 mol of Mg and sintered. The sintering conditions were varied over a temperature range of 600–1000 °C for 1, 3, and 7 h, respectively. The addition of Mg during the sintering increased the partial pressure of Mg and thus suppressed the decomposition of MgB2. Onset of critical temperature, Tc, was retained at ∼ 38 K even after the addition of Mg. By increasing the sintering temperature, magnetic critical current density, Jc at self-field, and 20 K of the ex situ samples increased consistently. With the addition of Mg for 1 h sintering, self-field Jc (20 K) was enhanced more than 20 times to 104 A cm−2 as the sintering temperature was increased. Such significant enhancement in the Jc is mainly due to the improved grain coupling aided by Mg during the short sintering.